2004
DOI: 10.1021/ic020727j
|View full text |Cite
|
Sign up to set email alerts
|

The Weakly Coordinating Trichloromethanesulfonate Anion:  NQR Comparison of Its Coordinating Abilities via Oxygen with Those of the Chloroacetate Ions

Abstract: Ionic and covalent derivatives of the chlorine analogue of the nonbasic, weakly coordinating triflate ion, Cl3CSO3(-) or "trichlate" ion, have been prepared and compared with the corresponding more strongly coordinated chloroacetates, Cl(x)CH(3-x)CO(2)M (x = 1-3), using 35Cl NQR (nuclear quadrupole resonance) spectroscopy. The (35)Cl NQR frequencies of all types of derivatives are sensitive to the nature of the metal ion or Lewis acid and are most sensitive in the case of monochloroacetates. In covalent (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…With the exception of the silver salt, the spectral widths of the dichloromethanesulfonates do Signal-to-noise ratios are given in parentheses not exceed 1.0 MHz, and thus do not exceed the normal (small) spectral width ( ν between the highest and the lowest NQR frequency at 77 K) due to crystallographic inequivalence of chlorines of less than about 0.8 MHz for molecular compounds and less than perhaps 1.5 MHz in ionic chloroacetates [3]. This is in sharp contrast to the large spectral widths of 2.075 MHz found in Na…”
Section: Average Nqr Frequency (Mhz)mentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of the silver salt, the spectral widths of the dichloromethanesulfonates do Signal-to-noise ratios are given in parentheses not exceed 1.0 MHz, and thus do not exceed the normal (small) spectral width ( ν between the highest and the lowest NQR frequency at 77 K) due to crystallographic inequivalence of chlorines of less than about 0.8 MHz for molecular compounds and less than perhaps 1.5 MHz in ionic chloroacetates [3]. This is in sharp contrast to the large spectral widths of 2.075 MHz found in Na…”
Section: Average Nqr Frequency (Mhz)mentioning
confidence: 99%
“…1 a Dichloromethanesulfonate ion (at left); b dichloromethanesulfonyl chloride synthesized earlier and was shown by X-ray crystallography and 35 Cl NQR (nuclear quadrupole resonance) spectroscopy to have Ag-Cl coordination (organochlorine coordination to Ag + produces a relatively large shift of 35 Cl NQR frequencies to lower values) [2]. Silver (I) trichloromethanesulfonate Ag + (Cl 3 CSO − 3 ) [3] was also synthesized; NQR indicated that it did not have such coordination [3]. Although silver dichloromethanesulfonate, Ag + (Cl 2 CHSO − 3 ), was synthesized by Senning et al [4], it was not structurally characterized; like CHCl 3 , it contains three strongly electron-withdrawing groups which may hinder coordination of the organochlorines to the silver ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I bond in [Ag(I 2 CH 2 ) 2 ] (PF 6 ) is secondary, with no sp hybridization, substitution of the observed η in equation (6) gives a value for σ B2 of 0.162; this corresponds to the donation of the slight δ found in neutral CH 2 I 2 , 0.15 e − , to Ag + to give a neutral iodine atom in the complex. However, use of the quadrupole coupling constants of the free and complexed ligand in equations analogous to equations (8) or (9) give significantly different σ B2 values of 0.067 and 0.080.…”
mentioning
confidence: 97%
“…The Schiff base formed from 2-chloroaniline and 2,6-dichlorobenzaldehyde undergoes oxidative addition to Mo(CO) 6 (8) and (9) allows us to estimate σ B2 = 0.134 -0.161. This large value can be justified by noting that Period 5 metal ions give larger crystal field stabilization energies than do Period 4 metal ions, especially when strongfield ligands such as CO are present.…”
mentioning
confidence: 99%